2015
DOI: 10.3109/10408363.2015.1051659
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory markers predicting severity of acute pancreatitis

Abstract: Acute pancreatitis (AP) is an inflammatory disease of highly variable severity, ranging from mild cases with low mortality to severe cases with high mortality. Numerous biomarkers have been studied as potential early predictors of the severity of this disease so that treatment can be optimally tailored to prevent complications. We aim to present and discuss the most relevant biomarkers for early severity assessment in AP that have been studied to date. We review the current literature on biomarkers that have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
135
1
14

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(156 citation statements)
references
References 96 publications
6
135
1
14
Order By: Relevance
“…We did not find any significant association between aspirin use and CRP, measured at the time of admission. Previous studies demonstrated that CRP level peaks after 48 hours of admission [27,28], and therefore measurement at the time of admission may have yielded a different result.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…We did not find any significant association between aspirin use and CRP, measured at the time of admission. Previous studies demonstrated that CRP level peaks after 48 hours of admission [27,28], and therefore measurement at the time of admission may have yielded a different result.…”
Section: Discussionmentioning
confidence: 79%
“…Various studies have used different cut-off points to differentiate mild and severe AP [26,28]. Unfortunately, it is neither disease-specific nor the absolute values are accurate at predicting necrosis or organ failure [28].…”
Section: Discussionmentioning
confidence: 99%
“…However, these scoring systems are quite complex. Although some can be investigated during presentation, for others it may be necessary to wait for 48 or 72 h. Several laboratory markers have been studied in order to predict the severity of AP, such as acute phase proteins, cytokines and adhesion molecules [30, 31]. However, when these serum markers are used alone, their specificity is generally low.…”
Section: Discussionmentioning
confidence: 99%
“…An ideal prognostic marker is needed to show the severity of the disease in the early period and as a guide to treatment. Studies have suggested that parameters associated with coagulation disorder and inflammation, thought to play a significant role in the pathogenesis of the disease, can be used for his purpose [10, 18-20, 30, 31]. …”
Section: Discussionmentioning
confidence: 99%
“…Microvascular changes may lead to increased pancreatic vascular permeability, oedema, haemorrhage and pancreatic necrosis. These hypotheses have led to detection of novel molecular therapeutic targets such as tumour necrosis factor -α and interleukin-6, both important activators of the inflammatory response in AP 12. A recent Cochrane review including 84 randomised controlled trials (RCTs) examined the efficacy of specific medical therapies in the treatment of AP; however, none of these showed clinical benefit or decreased short-term mortality over standard supportive treatment with intravenous fluids, electrolytes and organ support 13.…”
Section: Pathophysiologymentioning
confidence: 99%